(untitled) (Research, Society and Development, 2021)
Dentist community needs to understand the esthetic perception of laypeople and correlate the standards of dental esthetics to avoid unnecessary treatment. Thus, the aim was to compare the perception of smile attractiveness before and after performing esthetic dental procedures by general practitioners (GP), periodontists (P), restorative dentistry (RD), undergraduate students (UGrad), and laypeople (L). Two photographs of smile were taken, before (PSB) and after (PSA) the esthetic dental procedures. Photographs were exposed to 5 groups: GP (n = 20), P (n = 20), RD (n = 20), UGrad (n = 60), and L (n = 20). The smiles were evaluated using the visual scale with scores ranging from 1 (unattractive) to 10 (very attractive). Data were statistically evaluated (Kruskal-Wallis, Dunn, Mann Whitney). The PSA of the esthetic dental procedures was more attractive than PSB (p < 0.05). In PSB, P group presented the lowest values of smile attractiveness scores (p < 0.05). On the other hand, in PSA, RD group attributed lower values (p < 0.05). The perception of smile attractiveness after performing dental procedures was higher than before, and P and RD were more critical in evaluating the smiles before and after treatment, respectively.